Preparation, Shelf, and Eating Quality of Ready-to-Eat “Guichang” Kiwifruit: Regulation by Ethylene and 1-MCP - Yan, Han; Wang, Rui; Ji, Ning; Cao, Sen; Ma, Chao; Li, Jiangkuo; Wang, Guoli; Huang, Yaxin; Lei, Jiqing; Ba, Liangjie (Frontiers in Chemistry, 2022)
Consumer acceptance of kiwifruit is significantly affected by its slow ripening and susceptibility to deterioration. Herein, instant kiwifruit and its preparation technology were studied by the regulation of ethylene and 1-MCP. Harvested kiwifruit fruits is treated with 100~2000 μL L-1 ethylene for 36 h (20 ℃), followed by treatment with 0~0.5 μL L-1 1-MCP. The results show that the preservation effect of 0.5 μL L-1 1-MCP is inefficient when the soluble solids content (SSC) of kiwifruit exceeded 15 %. The ethylene-treated fruits reached an “edible window” after 24 h, but a higher concentration of ethylene did not further improve ripening efficiency. While, the optimal concentration was 250 μL L-`1. Moreover, after 250 μL L-`1 ethylene treatment, 0.5 μL L-`1 1-MCP effectively prolonged the “edible window” of fruits by approximately 19 d. The volatile component variety and ester content of 0.5 μL L-11-MCP-treated fruits were not different from those of the CK group. Principal component analysis (PCA) and hierarchical cluster analysis (HCA) indicated that the eating quality of fruits treated with 0.5 μL L-1 1-MCP was similar to that of fruits treated with ethylene. Consequently, instant kiwifruit preparation includes ripening with 250 μL L-1 (20 ℃, 36 h) ethylene without exceeding the 1-MCP threshold and then treating with 0.5 μL L-1 1-MCP (20 ℃, 24 h). This study highlights the first development of a facile and low-cost preparation technology for instant kiwifruit, which could reduce the time for harvested kiwifruit to reach the “edible window” and prolong the “edible window” of edible kiwifruit.